Le chef scout canadien-français : son idéal, sa formation et sa mission dans quatre troupes d’Outremont (1935-1965) - Boudreau, David (Université de Montréal, 2011)
The Quebec Federation of catholic scouts was founded in 1935. Its goals were demanding: it proposed to train men, Christians and citizens. Moreover, it intended to train leaders who could influence the French-Canadian society. Although headed by the Catholic Church, the Francophone Quebec scout movement was in fact dominated and directed by laymen. The Scoutmaster (SM) and the Patrol Leader (PL) were the two main lay leaders of the scout troop. They were respectively in charge of the troop (24-32 youths) and the patrol (6-8 youths). The PL was a young scout himself. The ideals and system representations conveyed to youths were transmitted through the SM and PL. They needed to be trained appropriately to respect their commitment. Beyond the regular competencies of a leader, their training proposed to transmit nothing less than an authentic dealing with the world: the ideal of Scoutmaster. Taking the scout method recommended by the Federation as a formal background, this dissertation analyses its true life actualization by Scoutmasters and Patrol Leaders of four Outremont troops. The impact of the Quiet Revolution on the traditional representation of the boyscout leader is also examined.
Keywords: Boy scouting; Catholic; Catholique; History - Canadian / Histoire - Canadienne (UMI : 0334); Leadership; Outremont; Quebec; Québec; Scoutisme